Palm Oil Workers Employment Policy and Sustainability - Lionardo, Andries; Kurniawan, Rudy; Irmawati, Irmawati; Umanailo, Muhamad Chairul Basrun; Santoso, Anang Dwi (ARISTO, 2025)
Employment policies in Indonesia's palm oil industry often have a significant impact on palm oil workers. Many of the government's efforts to appreciate the existence of workers through regulations have stalled due to low participation by plantation owners and companies. The reality of palm oil workers in Musi Banyuasin Regency indicates the weak knowledge of workers and low participation by plantation owners, which results in a lack of security for palm oil workers' livelihoods. This research uses a qualitative approach, collecting in-depth interviews and participant observation data. The research results show that workers' low understanding of labor regulations causes the working conditions of palm oil workers to become increasingly difficult, as does the low participation of plantation owners in the implementation of labor regulations, which makes regulations increasingly less functional as the main aim of making palm oil workers prosperous.